DIGITALISASI PELAYANAN PUBLIK DI BANDAR UDARA DENGAN MEMANFAATKAN CHATBOT RESPONSE - Anas Muzaki; Ariyono Setiawan; Fatmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In the industrial revolution 4.0, there were many advances developments from the digital technology sector where makes it easier for humans to do various jobs, for example the barcode system to make it easier just by scanning, websites for online promotion places, chatbot responses to answer questions quickly, and public services with many concepts starting to be developed and used for a more effective and attractive process.Development of public services at the airport by using the chatbot response feature that makes it easier to answer questions that asked by users or visitors, where the website has interesting features. In addition, users and visitors can provide an assessment of the facilities at Ngloram Cepu Airport for future improvement of facilities. The place of the facility shown is accompanied by a picture and description of the name. The method used in this research is Research and Development (R&D), with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model development procedure.The digitalization of public services using a chatbot response has been tested on online users and visitors and can be used as a supporting tool in the evaluation conducted at Cepu Ngloram Airport.